Risk factors for horse fatality in thoroughbred jumps racing in New Zealand - Gibson, M. J.; Legg, K. A.; Gee, E. K.; Rogers, C. W. (Journal of Equine Veterinary Science, 2023)
The aim of this study was to examine the race-, horse- and jockey-level risk factors for race day fatality in New Zealand Thoroughbred jumps racing using retrospective race day data from the 2011/12 to 2021/22 seasons (n = 8,970 starts). There were 51 race day fatalities resulting in an incidence rate of 5.7 per 1,000 starts (95% C.I. 4.3-7.5). The majority of fatalities were the result of fractures (44/51, 4.9 per 1,000 starts, 95% C.I. 3.7-6.6). Steeplechase and hurdle races had the same incidence of fatal fractures of 4.9 per 1,000 starts (95% C.I. 3.7-6.6, P > .05). Most (70.5%) of the fatal fractures were due to a horse falling during the race. In steeplechase races, horses running in races over 4,201 m were 5.0 times (95% C.I. 1.2-33.0) more likely to sustain a fatal fracture than horses in racing over shorter distances. In hurdle races, horses racing during spring were 2.2 times (95% C.I. 1.0-4.8) more likely to sustain a fatal fracture compared to winter. Due to the low number of suspected cardiac failures and fatal soft tissue injuries, risk factors for these fatalities could not be identified. These data provide a baseline to enable evidence-based regulatory changes and prospectively monitor the effectiveness of changes made.